OC-084 The targeted use of Taurolock® to reduce central venous catheter sepsis in a home parenteral nutrition cohort. (23rd September 2015) - Rafferty, G P; Nightingale, J; Small, M; Eastwood, J; UgarteCano, C; Gabe, S
Abstract : Introduction: Taurolock® (Bio-Implant HealthCare, Winsen, Germany) is an anti-microbial agent (taurolidine) with anticoagulant properties (citrate). There is evidence that Taurolock® is beneficial in reducing catheter-related blood stream infections (CRBSI) in haemodialysis patients, but there are fewer data regarding benefit in home parenteral nutrition (HPN) patients.1 2 At St Mark's Intestinal Failure Unit Taurolock® is prescribed for patients with greater than three CRBSI in a 12-month period. The primary aim was to determine the incidence of CRBSI prior and subsequent to Taurolock® use. The secondary aim was to establish cost benefit from Taurolock® prescription. Methods: Retrospective audit using St Mark's Intestinal Failure (IF) Database. ::::CRBSI and Taurolock® prescription recorded on IF database. CRBSI defined as positive central venous catheter blood cultures with fever±rigors. Simple cost analysis calculated at £8340 per hospital treatment for CRBSI (10 day in-patient admission) and Taurolock costing £11 per day. Results: All 16 patients (male 56.3%, mean age 44.8 years (range 23–73)) prescribed Taurolock® were selected. In the pre-treatment group mean duration from first CRBSI episode to Taurolock® prescription was 602±317 days. This pre-treatment group had a mean 9.8±6.5 CRBSI rate per 1000 catheter days. The treatment group (mean duration 557±269 days) had a mean 3.3±3.4 CVC related sepsis rate per 1000 catheter days. There was a significant difference (p<0.001) in CRBSI rate prior and subsequent to Taurolock® prescription. Treating CRSBI for 1 year in these 16 patients pre-Taurolock® cost approximately £367 000 (440 in-patient days and antibiotic costs). Approximate treatment group costs were £228 240 (£164 000 hospital costs for treating CRBSI and £64 240 for Taurolock treatment). One year cost savings of Taurolock® prescription was £138 760. Conclusion: Taurolock® significantly decreases CRBSI rate in HPN patients. These results are in keeping with a Canadian group that managed to decrease CRBSI following treatment in seven patients. (2) Taurolock® prescription generates considerable cost savings in this cohort of patients.